Optimization of a nonviral transfection system to evaluate Cox‐2 controlled interleukin‐4 expression for osteoarthritis gene therapy in vitro. (November 2014) - Lang, Annemarie; Neuhaus, Johannes; Pfeiffenberger, Moritz; Schröder, Erik; Ponomarev, Igor; Weber, Yvonne; Gaber, Timo; Schmidt, Michael F. G.
Abstract: Background: Gene therapy appears to have the potential for achieving a long‐term remedy for osteoarthritis (OA). However, there is a risk of adverse reactions, especially when using cytomegalovirus‐controlled expression. To provide a safe application, we focused on the expression of therapeutic cytokines [e.g. interleukin (IL)‐4] in a disease‐responsive manner by use of the previously cloned Cox‐2 promoter as 'genetic switch'. In the present study, we report the functionality of a controlled gene therapeutic system in an equine osteoarthritic cell model. Methods: Different nonviral transfection reagents were tested for their efficiency on equine chondrocytes stimulated with equine IL‐1β or lipopolysaccharide to create an inflammatory environment. To optimize the transfection, we successfully redesigned the vector by excluding the internal ribosomal entry site (IRES). The functionality of our Cox‐2 promoter construct with respect to expressing IL‐4 was proven at the mRNA and protein levels and the anti‐inflammatory potential of IL‐4 was confirmed by analyzing the expression of IL‐1β, IL‐6, IL‐8, matrix metalloproteinase (MMP)‐1, MMP‐3 and tumor necrosis factor (TNF)‐α using a quantitative polymerase chain reaction. Results: Nonviral transfection reagents yielded transfection rates from 21% to 44% with control vectors with and without IRES, respectively. Stimulation of equine chondrocytes resulted in a 20‐fold increase of mRNA expression of IL‐1β. Such exogenous stimulation of chondrocytes transfected with pNCox2‐IL4 led to an increase of IL‐4 mRNA expression, whereas expression of inflammatory mediators decreased. The timely link between these events confirms the anti‐inflammatory potential of synthesized IL‐4. Conclusions: We consider that this approach has significant potential for translation into a useful anti‐inflammation therapy. Molecular tools such as the described therapeutic plasmid pave the way for a local‐controlled, self‐limiting gene therapy. Copyright © 2014 John Wiley & Sons, Ltd.